Marketing Activities of Polish Banks Evaluation Attempt - Grzegorczyk, Wojciech (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Assessing the appropriateness of marketing activities of banks and their effectiveness is difficult because of the reluctance of banks to provide information on these activities, expenditure incurred and their effects. Furthermore, there hasn’t been kept statistics in that respect for the banking sector as a whole. Most banks do not keep reports of marketing expenditures on individual marketing efforts – such as the creation of new products, analysis of the market situation, the analysis of simulation of consumer behavior to price changes, etc. Therefore, it is possible to make only very general conclusions about the effects of marketing activities of banks. A marketing strategy of a bank is an element of an overall strategy of the bank and it is no the sole factor contributing to the positive results of the strategy. Its impact, however, is significant. It is assumed that properly prepared and executed marketing activities allow banks to achieve the intended goals.